The Role of Leadership, Work Climate, and Motivation in Enhancing Teacher Performance - Nursofah; Muryani, Sri (Jurnal Manajemen Pendidikan, 2025)
Background Teacher performance plays a crucial role in enhancing educational quality, and several factors such as leadership, work climate, and work motivation may influence it. Understanding how these variables interact can inform educational practices and improve overall teaching effectiveness. Purpose The purpose of this study is to examine the impact of leadership, work climate, and work motivation on teacher performance in an educational setting. Design/Method/Approach This research uses a quantitative approach with a hypothesis testing methodology. Data were collected through surveys from a sample of teachers, and statistical analyses, including t-tests and p-value calculations, were employed to test the hypotheses. Results The findings reveal that all three variables leadership, work climate, and work motivation significantly influence teacher performance. Specifically, the t-test results for leadership, work climate, and work motivation were 2.058, 2.242, and 3.958, respectively, and the corresponding p-values were 0.029, 0.025, and 0.000, all indicating statistical significance. Contribution/Value This study contributes to the literature by providing empirical evidence on the relationship between leadership, work climate, work motivation, and teacher performance. The results offer valuable insights for educational policymakers and school leaders aiming to enhance teacher performance and overall school effectiveness.